Which Extent is Plasticity to Light Involved in the Ecotypic Differentiation of a Tree Species from Savanna and Forest? - Goulart, Maíra F.; Lovato, Maria B.; de Vasconcellos Barros, Fernanda; Valladares, Fernando; Lemos-Filho, José P. (Biotropica, 2011)
Light intensity and heterogeneity are some of the main environmental factors that differ between forest and savanna habitats, and plant species from these habitats form distinct functional types. In this study, we tested the hypothesis that not only differences in morphological and physiological traits but also phenotypic plasticity in response to light are involved in adaptation to forest and savanna habitats by investigating ecotypic differentiation between populations of Plathymenia renculata (Leguminosae: Mimosoideae), a tree from the Brazilian Atlantic Forest and the Brazilian Cerrado (savanna). Seeds from four natural populations (one from each biome core area and two from ecotonal regions) were grown in a common garden with four light treatments. Fifteen morphological and physiological characteristics were evaluated until individuals reached 6 mo old. Comparisons among populations showed differences for seven traits in at least one light treatment. These differences pointed to local adaptation to different biomes. Populations showed different levels of phenotypic plasticity in response to light in seven traits. Higher plasticity was found either in the forest core population or ecotonal populations; lower values were found in the cerrado core population. Lower plasticity in the cerrado population emphasizes the stress resistant syndrome, as lower plasticity is probably advantageous in a habitat where a conservative resource use is crucial. Higher plasticity in forest individuals suggests higher ability in exploiting the light heterogeneity in this habitat. Also, higher plasticity in ecotonal populations can be important to ensure the maintenance of P. reticulata in these temporally and spatially dynamic areas.